Faktor-Faktor Pembangunan di Kawasan Lereng Bukit Yang Menyumbang Kepada Risiko Keselamatan Terhadap Penduduk Sekitar - Jomling, Polly; Shafii, Haryati; Masram, Haidaliza; Omar, Roshartini; Mohamed, Sulzakimin; Kai Chen, Goh; Ibrahim, Mohd Hairy (Research in Management of Technology and Business, 2023)
The hillside area is exploited as a development area that can pose a safety risk to the surrounding people. The problem statement of this study is development issues in hillside areas that contribute to safety risks for the surrounding people. The objective is to identify the factors of development in hillside areas that contribute to the safety of the surrounding residents, to study the impact of development in the hillside area on the safety of the surrounding residents and to study the measures taken by the authorities to overcome development in the hillside area. This study was conducted using the critical method of literature review analysis and analyzed using systematic analysis. This study focuses on development in hillside areas in Malaysia. The findings of the study found that development factors in hillside areas are such as the attitude of some developers who pursue profit, uncontrolled development and non-compliance with EIA. Next, the findings of the study also prove that development in hillside areas does indeed have a negative impact on the safety of the surrounding residents such as landslides, loss of life, loss of housing and even injuries. Further, the measures taken by the authorities to overcome development in hillside areas are such as controlling development especially involving hillsides and ensuring that developers comply with development guidelines in hillside areas. It is hoped that this study can help the parties involved to increase sensitivity, improve weaknesses and prioritize the safety of residents in a development involving hillside areas.